Adsorpsi Metilen Biru dan Kongo Merah pada Zeolit-A Hasil Sintesis dari Abu Dasar Batubara PT. Petrokimia Gresik - Widiastuti, Nurul; Fachruddin, Mochammad Harits; Setyaningsih, Endang Purwanti; Romadiansyah, Taufik Qodar (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Negeri Balikpapan, 2022)
The adsorption of methylene blue and congo red dye using zeolite-A synthesized from coal bottom ash and it comparison from synthetic materials has been studied with initial concentration variations between 60, 80, 100, 120, 140, 160, 180, 200 and 220 mg/L, contact time 10-100 min and temperature between 30, 40, 50 ºC with pH 6-7. Adsorption equilibrium time was achieved at contact time of 70-80 minutes for methylene blu dye and 40-50 minutes for congo red dye. Increased adsorption capacity significantly lead to methylene blue with maximum adsorption capacity achieved up to 67.57 mg/g and 70.73 mg/g, adsorption capacity on congo red adsorbate achieved 39.43 mg/g and 41.50 mg/g each for zeolite A from coal bottom ash and it comparison. The analysis of the kinetics adsorption equation shows that the adsorption process of methylene blue and congo red dye follows second-order pseudo kinetics model, but adsorption of methylene blue follows Freundlich isothermal equation, while adsorption of congo red follows Langmuir isothermal equation. The study of adsorption thermodynamics results that the capacity adsorption increased with the increasing of temperature. Adsorption process occurs endothermally and spontaneously at methylene blue and congo red dye.